Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T17:40:45+01:00
9y - 7 = 11 + 7 y
2y = 18 / :2
y = 9<tak jest prosciej >

ale chcesz tym drugim psosobem, wiec:

y = 7
9*7 -7 =11 +7*7
63-7 = 11+49
56 = 60 <nie jest sobie rowne>

y=8
9*8 -7 = 11 +7*8
72 - 7 = 11 +56
65 = 67 <nie jest sobie rowne>

y=9
9*9 -7 = 11+7*9
81-7 = 11+63
74 = 74

:)
2010-01-27T17:44:28+01:00
2010-01-27T17:45:53+01:00
Liczba 7

y=7
L=9*7-7
P=11+7*7
L=63-7
P=11+49
L=56
P=60

Liczba 8

y=8
L=9*8-7
P=11+7*8
L=72-7
P=11+ 56
L=65
P=67

LICZBA 9

y=9
L=9*9-7
P=11+7*9
L=81-7
P=11+63
L=74
P=74

ODPOWIEDŹ : To równanie spełnia liczba 9.